Peningkatan Kompetensi Personel PKP-PK Melalui Pelatihan Pengujian Kualitas Foam di Lingkungan Kantor Otoritas Bandar Udara Wilayah V Makassar - Supri, Supri; Saputra, Surya Tri; Kalbuana, Nawang; Wahyudono, Wahyudono; Abdusshomad, Alwazir; Sukra, Rahmawati (Jurnal Pengabdian Kepada Masyarakat, 2025)
Aviation safety is a crucial aspect that must be safeguarded, particularly in addressing the potential risk of fires in airport areas. To enhance personnel preparedness, an intensive training program on foam-based fire extinguishing agent testing was conducted by faculty members of the Aircraft Rescue and Firefighting (ARFF) Study Program, Indonesian Aviation Polytechnic of Curug, in collaboration with the Airport Authority Office Region V Makassar. The training aimed to equip ARFF personnel with both theoretical understanding and practical skills in evaluating foam quality to ensure its effective use in firefighting operations. The program employed a comprehensive approach, integrating theoretical lectures, demonstrations, simulations, and hands-on practice in testing various parameters of fire extinguishing agents. The outcomes highlighted that key parameters—such as expansion ratio, drainage time, and resistance to fuel contamination play a significant role in determining firefighting effectiveness. Furthermore, the importance of regular equipment maintenance and the utilization of the latest testing technologies was strongly emphasized throughout the training. Through this community service initiative, it is expected that the competence of ARFF personnel will be substantially enhanced, enabling them to respond more effectively to airport fire emergencies, thereby reinforcing the overall national aviation safety system.